Scanning electron microscopy imaging to assess bone implant contact enhancement after immediate bioactive compound placement - Muthia Mutmainnah Bachtiar; Edy Machmud; Andi Ajmal (Indonesian Journal of Prosthodontic, 2023)
Along with the increasing use of implant-supported dentures, the use of biomaterials to accelerate the process of new bone formation is favorable. Chlorella vulgaris is a natural product that contains elements of calcium, minerals, and vitamin D acting in mineralizing bones and teeth. In addition, the content of flavonoids and phenols in Chlorella vulgaris that are applied topically can inhibit TNF-a therefore inducing bone healing. This study aims to assess the effect of bioactive material on bone implant contact (BIC) by using SEM imaging. Nine Landrace pigs were used in this study and surgical procedures were performed in the mandible. Chlorella vulgaris extract gel was placed in the left socket and without gel in the right socket, afterward followed by titanium implant placement. Both treatments were carried out in the same way, then three pigs were observed per one time period, namely the 30th, 60th, and 90th days by using SEM test. The BIC of the sample showed the greatest at day 90th after application of gel and implant placement. It is concluded that the use of bioactive material, gel extract Chlorella vulgaris 15%, can stimulate the osseointegration better, and improve the BIC percentage.